Alpha-whey protein nanoparticles as well as preparation and application thereof

The α-whey protein nanoparticle carrier prepared by electrostatic spraying process loads fibroblast growth factors and achieves slow-controlled release, solving the problem of poor stability of active ingredients in existing wound dressings, significantly improving the therapeutic effect and the bioavailability of the drug.

CN119746087APending Publication Date: 2025-04-04SHENYANG PHARMA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411819365.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing wound dressings based on fibroblast growth factor have problems with poor stability of active ingredients and require multiple doses, which affects patient compliance and treatment effect.

Method used

Alpha-whey protein nanoparticles were prepared by electrostatic spraying. By complexing α-whey protein with calcium ions, a structurally stable carrier was formed, and fibroblast growth factor was loaded on it to achieve slow-controlled release.

Benefits of technology

It significantly improves the biostability and therapeutic activity of fibroblast growth factors, achieves continuous release and synergistic treatment effects in the wound microenvironment, and improves the bioavailability and targeting of drugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746087A_ABST
    Figure CN119746087A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of biological medicines, and particularly relates to alpha-whey protein nanoparticles as well as preparation and application thereof. The invention relates to an alpha-whey protein nanoparticle which is a stable-structure alpha-whey protein nanoparticle obtained by complexing alpha-whey protein and calcium ions through an electrostatic spraying process. The preparation process is simple, the conditions are mild, the cost is low, the prepared nanoparticles provide effective protection and slow release for bioactive macromolecules with poor in-vivo stability, the biological activity of the alpha-whey protein carrier can be effectively maintained, and the synergistic treatment effect of the two active protein molecules is achieved. The invention provides a novel nano-drug delivery treatment strategy for complex diseases such as wound healing, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedicine, and specifically relates to alpha-lactalbumin nanoparticles and preparation and application thereof. Background Art

[0002] According to the World Health Organization, millions of people suffer from skin burns every year, and the healing of burn wounds has become a global health problem. Burn wounds are divided into four levels according to the depth of burns: first-degree burns, shallow second-degree burns, deep second-degree burns and deep third-degree burns. Among them, in the whole wound area of ​​deep third-degree burns, the whole skin tissue is completely destroyed, including the stratum corneum, dermis and fat layer. Due to the complete damage of skin tissue, for patients with deep third-degree burns, if timely wound healing treatment is not performed, the acute burn wound will gradually develop into a chronic wound that is difficult to heal, and cause great harm to the body and mind.

[0003] Fibroblast growth factor has shown excellent biological activity in wound healing. It can promote wound healing by stimulating the proliferation and migration of fibroblasts and keratinocytes, promoting the maturation of the extracellular matrix and angiogenesis. However, as a biological macromolecular active substance, the inherent poor biological stability of fibroblast growth factor seriously affects its drugability. There are currently many marketed wound dressings based on fibroblast growth factor, such as Such drugs are mainly spray-based, and have problems and challenges such as poor stability of active ingredients and the need for multiple doses per day, which seriously affect patient compliance and treatment outcomes.

[0004] With the progress of medicine and materials science, nano drug delivery system, as an ideal wound dressing, can make active substances interact with wound tissue cells better, improve their stability in the tissue microenvironment, and target specific types of cells to better promote wound healing. Protein nanoparticles, as a new type of nano delivery carrier, not only have the unique spatial regulation flexibility of proteins, but also have the advantages of controlling drug release, enhancing drug stability, improving drug bioavailability and targeting, and play an important role in wound healing. At present, albumin, silk fibroin, and gelatin are commonly used as carrier protein biomaterials for nanoparticles for active substance delivery. Although these protein materials have good biocompatibility, they not only have low biological activity, but also change the protein conformation due to the addition of cross-linking agents during the preparation process, so that they cannot exert their own biological activity while delivering active substances, and produce synergistic therapeutic effects.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide an alpha-lactalbumin nanoparticle and its preparation and application.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] The invention discloses an alpha-lactalbumin nanoparticle, wherein the carrier is an alpha-lactalbumin carrier with a stable structure obtained by complexing the alpha-lactalbumin with calcium ions through an electrostatic spraying process.

[0009] The molar ratio of calcium ion to α-lactalbumin is 500:1-10:1; wherein the α-lactalbumin is derived from α-lactalbumin of cow's milk and has a molecular weight of 14.2 kDa.

[0010] A method for preparing α-lactalbumin nanoparticles comprises dissolving α-lactalbumin and polyoxyethylene in water, adding a salt containing calcium ions to the system after the dissolution, stirring and mixing to obtain a clear and transparent electrostatic spray solution, and then obtaining the α-lactalbumin nanoparticles by electrostatic spraying; wherein the final concentration of α-lactalbumin in the electrostatic spray solution is 2-8wt%, and the final concentration of polyoxyethylene is 0.1-0.7wt%.

[0011] The electrostatic spraying conditions are as follows: voltage of 15-23 kV, injection speed of 0.11-0.38 mL / h, receiving distance of 10-30 cm, temperature of the entire preparation system controlled at 30° C.±3° C., and relative humidity of 50%±5%.

[0012] The calcium ion-containing salt is one or more of calcium chloride, calcium bromide, calcium nitrate, calcium hydrogen carbonate, and calcium dihydrogen phosphate; preferably calcium chloride.

[0013] An application of the α-lactalbumin nanoparticles, wherein the α-lactalbumin nanoparticles are used as a delivery system.

[0014] The invention discloses alpha-lactalbumin nanoparticles loaded with cell growth factors, wherein the nanoparticles contain the alpha-lactalbumin nanoparticles.

[0015] A method for preparing alpha-lactalbumin nanoparticles loaded with cell growth factors comprises dissolving alpha-lactalbumin and polyoxyethylene in water, adding salt containing calcium ions to the system after dissolution, stirring and mixing to obtain a clear and transparent electrostatic spray solution, and simultaneously performing electrostatic spraying and electrostatic spinning to obtain the alpha-lactalbumin nanoparticles loaded with cell growth factors.

[0016] The working environment temperature of the electrostatic spinning machine is 15° C.-35° C., and the working humidity is 35%-75%.

[0017] The α-lactalbumin nanoparticles loaded with fibroblast growth factor are mainly made of α-lactalbumin (ALA), a salt containing calcium ions (for example, calcium chloride (CaCl2)), a fibroblast growth factor (FGF) and polyoxyethylene (PEO): the molar ratio of CaCl2 to ALA is 500:1-10:1 (for example, 500:1, 250:1, 150:1, 100:1, 50:1, 0:1), preferably 100:1; the molecular weight of PEO is 100-1000kDa, preferably 300kDa.

[0018] There is no particular limitation on the fibroblast growth factor, and it may be any fibroblast growth factor known in the art for wound healing treatment, preferably a recombinant human fibroblast growth factor, with a concentration of 1-100 μg / mL.

[0019] An application of the alpha-lactalbumin nanoparticles loaded with cell growth factors, and an application of the alpha-lactalbumin nanoparticles loaded with cell growth factors in the preparation of wound healing drugs.

[0020] Furthermore, when preparing nanoparticles, electrostatic spraying and electrostatic spinning are performed simultaneously to encapsulate the α-lactalbumin nanoparticles loaded with fibroblast growth factor on the polymer nanofiber network, thereby preparing wound healing drug dressings.

[0021] Furthermore, the preparation method of the wound healing medicated dressing comprises the following steps:

[0022] 1) dissolving ALA, CaCl2, FGF and PEO in water to obtain an electrostatic spray solution;

[0023] 2) placing the electrostatic spray solution in an electrospinning machine for electrostatic spraying, and collecting α-lactalbumin nanoparticles loaded with fibroblast growth factor.

[0024] 3) Dissolving the polymer material in water to obtain an electrospinning solution.

[0025] 4) placing the electrostatic spray solution and the electrostatic spinning solution in an electrostatic spinning machine, performing electrostatic spraying and electrostatic spinning simultaneously, and collecting the nanofiber membrane encapsulating the α-lactalbumin nanoparticles loaded with fibroblast growth factor.

[0026] In the above steps 1) and 3), the water is ultrapure water.

[0027] In the above step 2), the electrostatic spray needle model is 20-27G, preferably 27G; the spray voltage is 15-23kV, preferably 23kV; the injection speed is 0.11-0.38mL / h, preferably 0.23mL / h; the working environment temperature is 15℃-35℃, preferably 30℃; the working humidity is 35%-75%, preferably 50%.

[0028] In the above step 3), the polymer material is a hydrophilic polymer material, including carboxymethyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, gelatin, etc., preferably polyvinyl alcohol, more preferably polyvinyl alcohol 17-88.

[0029] The use of the α-lactalbumin nanoparticles loaded with cell growth factors in the preparation of a drug for healing skin wounds caused by burns and scalds; more preferably, for healing skin wounds caused by deep III degree burns and scalds.

[0030] The advantages of the present invention are:

[0031] The drug dressing of the present invention exerts the biological activity of fibroblast growth factor and the carrier delivery ability of ALA to encapsulate biomacromolecule drugs, fully utilizing the "salt bridge effect" between the molecular structure and calcium ions to accurately deliver the drug to the wound site and slowly release it in the wound microenvironment, significantly improving the biological stability and therapeutic activity of the drug. The present invention utilizes ALA to deliver fibroblast growth factor, and the α-lactalbumin nanoparticles loaded with fibroblast growth factor prepared by the electrostatic spray method can effectively improve the poor in vivo stability, low bioavailability, and weak targeting ability of biomacromolecule drugs. It has the following advantages:

[0032] (1) Biosafety: Fibroblast growth factor is a recombinant human fibroblast growth factor, which is highly endogenous; α-lactalbumin and polyvinyl alcohol as carriers are both biodegradable; calcium ions are a macronutrient for the human body and are an indispensable nutrient.

[0033] (2) Sustained release: The complex structure formed by α-lactalbumin and calcium ions can stably encapsulate fibroblast growth factor and slowly release it in the wound environment, so that the fibroblast growth factor can continue to produce a therapeutic effect during the wound healing process.

[0034] (3) Targeting: α-lactalbumin nanoparticles can be taken up by skin tissue matrix cells, including fibroblasts and keratinocytes, thereby achieving intracellular delivery of biomacromolecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1The scanning electron microscopy images of ALANPs prepared with different ALA and PEO concentrations in Example 1;

[0036] Figure 2 The scanning electron microscope images of ALANPs prepared with different process parameters in Example 2;

[0037] Figure 3 For different Ca in Example 3 2+ In vitro release profiles of ALANPs loaded with BSA(FITC) prepared at molar ratios with ALA;

[0038] Figure 4 This is an investigation of the effects of different pretreatment conditions on the stabilization of FGF activity by FGF@ALANPs in Example 5;

[0039] Figure 5 This is the cell uptake experiment of FGF@ALANPs on NIH-3T3 cells and HaCaT cells in Example 5; wherein A is a laser confocal microscope fluorescence image, and B is a flow cytometry histogram and a statistical graph of the average fluorescence intensity.

[0040] Figure 6 This is a schematic diagram of the preparation process of the nanofiber membrane encapsulating nanoparticles in Example 6;

[0041] Figure 7 This is a scanning electron microscopy image of the FGF-loaded nanofiber membrane in Example 6

[0042] Figure 8 The scanning electron microscopy images of nanofiber membranes loaded with nanoparticles prepared by different polymers in Example 6;

[0043] Fig. 9 The in vitro release profile of the nanofiber membrane encapsulating nanoparticles in Example 6;

[0044] Fig.10 This is an in vivo pharmacodynamic experiment on the healing of deep III degree burn wounds by the nanofiber membrane encapsulated with nanoparticles in Example 6; wherein A is a wound photo; and B is a statistical analysis of the wound healing rates of each group. DETAILED DESCRIPTION

[0045] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.

[0046] The present invention adopts a simple electrostatic spraying method to prepare α-lactalbumin nanoparticles loaded with fibroblast growth factor in one step, and the method is simple, low-cost and mild conditions; the provided α-lactalbumin nanoparticles loaded with fibroblast growth factor have good biosafety and biotargeting; at the same time, the α-lactalbumin nanoparticles loaded with fibroblast growth factor can effectively protect the in vivo stability of the loaded drug and have effective sustained and controlled release ability; compared with other nanoparticles with proteins as carriers, such as serum albumin and other carrier proteins without biological activity, the nanoparticles provided by the present invention use α-lactalbumin with wound healing activity, and achieve the synergistic therapeutic effect with fibroblast growth factor. The α-lactalbumin nanoparticles have good biosafety, targeting, sustained and controlled release ability and synergistic treatment characteristics, successfully construct a delivery system for α-lactalbumin-encapsulated bioactive macromolecules, and prepare a new healing dressing for efficient and safe treatment of skin wound healing and other tissue regeneration diseases, which has broad application prospects and clinical transformation potential.

[0047] The nanoparticles of the present invention are synthesized by an electrostatic spraying method, and mainly utilize the natural molecular-ion interaction force between the calcium ion binding domain and the metal cation that are specially present in the alpha-lactalbumin molecule to form a stable complex, thereby realizing the effective loading and delivery of biologically active macromolecules such as fibroblast growth factor. The preparation process of the present invention is simple, the conditions are mild, and the cost is low. The prepared nanoparticles not only provide effective protection and slow release for biologically active macromolecules with poor stability in vivo, but also the biological activity of the alpha-lactalbumin carrier can be effectively maintained, realizing the synergistic therapeutic effect of the two active protein molecules. The present invention provides a new nano drug delivery treatment strategy for complex diseases such as wound healing, and has good application prospects.

[0048] Example 1: Preparation of blank α-lactalbumin nanoparticles

[0049] Weigh different masses of ALA and PEO and mix them in ultrapure water (the solution contains different masses of ALA and PEO, that is, the mass concentration of ALA is 2.0wt%, 5.0wt%, 8.0wt%, or the mass concentration of PEO is 0.1wt%, 0.3wt%, 0.7wt%), stir for 1h to completely dissolve, then add calcium chloride dihydrate (the molar ratio of calcium chloride dihydrate to ALA is 100:1) and stir at low speed for 5min to obtain a clear and transparent electrostatic spray solution. Then, the solution is loaded into a 2.0mL disposable syringe, the syringe is installed on the electrospinning machine, and the appropriate process parameters are set for electrostatic spraying: the voltage is 23kV, the needle model is 27G, the injection speed is 0.23mL / h, the receiving distance is 10cm, and the temperature of the entire preparation system is controlled at 30℃±3℃, and the relative humidity is 50%±5%. Finally, the blank α-lactalbumin nanoparticles (ALANPs) were collected from the receiving paper and stored in a desiccator.

[0050] The ALA is derived from α-lactalbumin in cow's milk and has a molecular weight of 14.2 kDa.

[0051] The molecular weight of PEO is 300 kDa.

[0052] Take an appropriate amount of the preparation and stick it on the conductive glue on the conductive sample stage. After it is left to stand at room temperature and stabilized, gold is sprayed for 45 seconds under vacuum. The microscopic morphology and particle size of the nanoparticles are observed using a scanning electron microscope. The results are as follows: Figure 1 .

[0053] Depend on Figure 1 It can be seen that when the ALA content is 2.0%, many small beads are formed between the particles; when the ALA content is 5.0%, the nanoparticles are uniform in morphology; when the ALA content is 8.0%, the particle size increases significantly, and the particles begin to change from spherical or quasi-spherical to irregular shapes. When the PEO content is 0.1%, the spray particle structure cannot be formed; when the PEO content is 0.3%, a nanoparticle structure with uniform morphology is formed; when the PEO content is 0.7%, the particle size increases significantly to the micron level, and the particle morphology is irregular. This may be because PEO is added to the ALA solution, which changes the properties of the ALA aqueous solution and improves the feasibility of electrostatic spraying of the solution. Therefore, a spray solution with an ALA content of 5.0% and a PEO content of 0.3% is preferred.

[0054] Example 2

[0055] ALA and PEO were mixed and dissolved in ultrapure water (the final concentration of ALA in the solution was 5.0%, and the final concentration of PEO was 0.3%), stirred for 1 hour to completely dissolve, and then calcium chloride dihydrate (the molar ratio of calcium chloride dihydrate to ALA was 100:1) was added and stirred at low speed for 5 minutes to obtain a clear and transparent electrostatic spray solution. The solution was then loaded into a 2.0mL disposable syringe, the syringe was installed on an electrospinning machine, and appropriate process parameters were set for electrostatic spraying: the voltage was 15-23kV (15kV, 20kV, 23kV,), the needle model was 20-27G (20G, 23G, 27G), the injection speed was 0.11-0.38mL / h (0.11mL / h, 0.23mL / h, 0.38mL / h,), the receiving distance was 10cm, and the temperature of the entire preparation system was controlled at 30℃±3℃, and the relative humidity was 50%±5%. Finally, the blank α-lactalbumin nanoparticles (ALANPs) were collected from the receiving paper and stored in a desiccator.

[0056] Depend on Figure 2 It can be seen that when the voltage is low (15 kV), no particle structure can be formed. As the voltage increases, the particle morphology gradually stabilizes, and when the voltage is 23 kV, a nanoparticle structure with uniform morphology is formed. Figure 2 It shows that when the injection speed is low (0.11mL / h), the spray jet is unstable, and the particles formed are extremely large and irregular in shape; when the injection speed is 0.23mL / h, a stable spherical particle structure can be obtained; when the injection speed is high (0.38mL / h), the solvent is not completely evaporated, and a particle structure with a complete morphology cannot be formed. As the spray needle gradually decreases, the prepared particles are uniform and have a complete morphology. This may be because as the inner diameter of the needle decreases, the critical electrostatic force that forms the Taylor cone at the needle tip decreases, which is conducive to the formation of a stable spray jet. Therefore, the preferred process parameters are a spray voltage of 23kV, an injection speed of 0.23mL / h, and a spray needle of 27G.

[0057] Example 3

[0058] ALA and PEO were mixed and dissolved in ultrapure water (the final concentration of ALA in the solution was 5.0%, and the final concentration of PEO was 0.3%), stirred for 1 hour to completely dissolve, and then different amounts of calcium chloride dihydrate were added (the molar ratio of calcium chloride dihydrate to ALA was 500:1, 250:1, 150:1, 100:1, 50:1, and 0:1, respectively) and stirred at low speed for 5 minutes to obtain a clear and transparent electrostatic spray solution. The solution was then loaded into a 2.0 mL disposable syringe, which was installed on an electrospinning machine, and appropriate process parameters were set for electrostatic spraying: the voltage was 23 kV, the needle model was 27 G, the injection speed was 0.23 mL / h, the receiving distance was 10 cm, the temperature of the entire preparation system was controlled at 30°C ± 3°C, and the relative humidity was 50% ± 5%. Finally, the blank α-lactalbumin nanoparticles (ALANPs) were collected from the receiving paper and stored in a desiccator.

[0059] The calcium ions (Ca) used in the preparation of nanoparticles 2+ ) dosage. Weigh 10.0 mg of the preparation, which contains Ca 2+ The molar ratios of ALA were 0:1, 10:1, 30:1, 50:1, 70:1, 100:1 and 150:1, respectively, and added to a 15 mL centrifuge tube containing 10.0 mL phosphate buffer (pH 6.5) and 0.1% sodium azide. The shaker was set to 100 rpm and the water bath temperature was 37°C. 1.0 mL of sample solution was taken at the specified time interval and centrifuged at 14000 rpm for 30 min to precipitate the solid sample. 200 μL of the supernatant was taken for detection, and then 200 μL of fresh release medium was added again and the sample solution was resuspended and added to the centrifuge tube. FITC-labeled bovine serum albumin (BSA (FITC)) was added to the preparation as a model biomacromolecule for detection: the fluorescence intensity in the sample was measured using an enzyme reader and substituted into the standard curve to calculate the content of BSA (FITC). All operations must be performed under light-proof conditions. The results are as follows. Figure 3 shown.

[0060] Depend on Figure 3 It can be seen that with the increase of Ca 2+ With the increase of Ca content, the controlled release ability of the obtained nanoparticles gradually increased. 2 + When the ratio of ALA to Ca is 100:1, its sustained-release capacity reaches the maximum and then begins to decline. 2+ The amount of ALA bound to the 2+ The binding capacity increases with the increase of Ca content, and after reaching a certain value, it begins to decrease. This may be due to excessive Ca 2+It will produce electrostatic repulsion inside the nanoparticles, thereby hindering the Ca 2+ The complexation between Ca and ALA reduces the stability of the particles. Therefore, in order to make the nanoparticles have better controlled release function, Ca is preferred. 2+ The nanoparticles were constructed with a ratio of 100:1.

[0061] Example 4: Preparation process of α-lactalbumin nanoparticles loaded with fibroblast growth factor

[0062] After preparing the blank spray solution (prepared according to the blank spray solution of Example 3, wherein Ca 2+ :ALA ratio is 100:1), different amounts of fibroblast growth factor (FGF) are added, and the mixture is placed in an electrostatic spray device after stirring for 10 minutes. Electrostatic spraying is performed according to the above-mentioned process parameters (voltage is 23 kV, needle model is 27G, injection speed is 0.23 mL / h, receiving distance is 10 cm, the temperature of the entire preparation system is controlled at 30°C ± 3°C, and the relative humidity is 50% ± 5%.), and α-lactalbumin nanoparticles loaded with fibroblast growth factor (ALA@FGF NPs) are collected and stored in a desiccant.

[0063] The amount of FGF used in the preparation of nanoparticles was investigated. The specific formulation is shown in Table 1. An appropriate amount of nanoparticles prepared as described above was taken, and the particle size and PDI of the preparation were determined using a Malvern dynamic light scattering instrument. The prepared nanoparticles were dissolved in water, centrifuged at 14000 rpm for 30 minutes to precipitate the solid sample, and then 200 μL of the supernatant was taken and tested using a fibroblast growth factor kit to determine the encapsulation efficiency (EE) of FGF in the preparation.

[0064] Table 1 FGF dosage prescription investigation

[0065]

[0066] There was no significant difference in particle size and PDI among the preparations prepared by the three formulations, but the EE (%) of formulation 3 was significantly reduced, which may be due to the excessively high FGF content. Therefore, the preferred FGF concentration is 100 μg / mL.

[0067] Example 5 Investigation of the properties of α-lactalbumin nanoparticles loaded with fibroblast growth factor The optimal formulation was selected for the preparation of nanoparticles, and the following investigations were conducted:

[0068] 1. Investigation of the protective effect of nanoparticles on the biological activity of FGF

[0069] The fibroblast growth factor solution (FGF), α-lactalbumin nanoparticles loaded with fibroblast growth factor (ALA@FGF NPs) obtained in prescription 2 of the above Example 4, and a blank control (PBS) were pretreated under five different conditions: untreated, standing at 4°C for 16 h, standing at 55°C for 2 h, standing at pH 5.0 for 16 h, and standing at 0.25% pancreatin for 16 h.

[0070] Then the pretreated samples and α-MEM complete medium containing the samples were added into 96-well plates seeded with NIH-3T3 cells (1.0×10 4 cells / well), and cultured in a cell culture incubator for 48 h. Then, 10 μL of CCK-8 solution was added to each well and incubated at 37°C for 2 h. The absorbance value (OD) at 450 nm was measured using an enzyme reader to calculate the cell survival rate.

[0071] Cell viability = (A 给药 -A 空白 ) / (A 对照 -A 空白 )×100%

[0072] The results are as follows Figure 4 As shown in the figure, under some relatively harsh environments, such as 55°C, pH 5.0 and 0.25% pancreatin environment, the FGF-promoting fibroblast proliferation activity was significantly reduced, indicating that the biological activity of FGF was significantly reduced under these environments. In addition, although the cell proliferation activity of the ALA@FGF NPs PVA group decreased, its ability to promote cell proliferation remained at a high level compared with the FGF PVA group, indicating that ALA@FGF NPs can protect the biological activity of FGF from the risk of decline under relatively harsh environments.

[0073] 2. Cellular Uptake of Nanoparticles

[0074] The ability of NIH-3T3 cells and HaCaT cells to take up nanoparticles was investigated. 5 cells / well) and HaCaT cells (4.0×10 5Cells / well) were inoculated in 6-well plates, and after the cells adhered, 2.0 mL of fresh culture medium (α-MEM complete culture medium containing 10% serum) and 10 mg of FITC-labeled nanoparticles (ALA nanoparticles loaded with FITC) were added to each well, and then cultured in a cell culture incubator for 4 hours. After trypsin digestion, the cells were resuspended in PBS to obtain a cell suspension, and the intracellular fluorescence intensity was analyzed by flow cytometry. Take another plate and perform the same operation as above. After co-incubation, the supernatant was discarded, the plates were washed 3 times with PBS, fixed with 4% paraformaldehyde, the cell nuclei were stained with DAPI staining solution, and observed and photographed with a fluorescence microscope. The results are shown in Figure 5 As shown, A is a fluorescence photograph; B and C are flow cytometric histograms and statistical analyses of the average fluorescence intensity after the nanoparticles were taken up by the two cells.

[0075] The results showed that both NIH-3T3 and HaCaT cells had fluorescent signals, indicating that both cells had a certain ability to absorb nanoparticles. Flow cytometry results further confirmed that compared with HaCaT cells, nanoparticles had a stronger cell entry efficiency in NIH-3T3 cells, indicating that nanoparticles had better selectivity for fibroblasts.

[0076] Example 6. Preparation and application of nanofiber membranes loaded with nanoparticles

[0077] 1. Preparation of Nanofiber Membranes Loaded with Nanoparticles

[0078] Weigh an appropriate amount of polymer material and dissolve it in water to prepare an electrospinning solution. Then prepare Example 3 (the blank carrier spray solution: ALA and PEO are mixed and dissolved in ultrapure water (the final concentration of ALA in the solution is 5.0%, and the final concentration of PEO is 0.3%), stir for 1 hour to completely dissolve, and then add calcium chloride dihydrate (the molar ratio of dihydrate and calcium chloride to ALA is 100:1) and stir at a low speed for 5 minutes to obtain a clear and transparent non-drug-loaded electrostatic spray solution. Then, the blank carrier nanoparticle nanofiber membrane (ALANPs / PVA) is prepared simultaneously with electrospinning) or Example 4 (The FGF-loaded spray solution: ALA and PEO were mixed and dissolved in ultrapure water (the final concentration of ALA in the solution was 5.0%, and the final concentration of PEO was 0.3%), stirred for 1 hour to completely dissolve, and then calcium chloride dihydrate (the molar ratio of dihydrate and calcium chloride to ALA was 100:1) and FGF (100 μg / mL) were added and stirred at a low speed for 5 minutes to obtain a clear and transparent FGF-loaded electrostatic spray solution. Then, the nanofiber membrane (ALA@FGF loaded with FGF nanoparticles) was prepared simultaneously with electrospinning. NPs / PVA)) is used as the electrostatic spray solution, and the electrostatic spray process is carried out synchronously during the electrostatic spinning process (installed on two push pumps in the electrospinning machine at the same time, and then the voltage and liquid supply are started at the same time, and the obtained nanoparticles and nanofibers are evenly sprayed on the same drum receiver to obtain a nanofiber membrane containing nanoparticles (blank nanoparticles or loaded FGF nanoparticles)). The temperature of the entire preparation system is controlled at 30°C ± 3°C, the relative humidity is 50% ± 5%, and the process is carried out according to the parameters in Table 2 below. Finally, the nanofiber membrane containing nanoparticles is collected and stored in a desiccator. The preparation process is as follows Figure 6 shown.

[0079] At the same time, appropriate amounts of polymer and FGF were weighed and dissolved in water to prepare an electrospinning solution. Then, according to the above electrospinning process parameters (spinning process parameters: voltage 23 kV, needle model 22G, injection speed 0.56 mL / h, receiving distance 10 cm. The temperature of the entire preparation system was controlled at 30°C ± 3°C, and the relative humidity was 25% ± 5%), a nanofiber membrane containing FGF was prepared as a control sample (such as Figure 7 and store in a desiccator.

[0080] 2. Investigation of nanofiber membrane material types

[0081] The types of polymer materials used in the nanofiber membrane were investigated. The specific formulations and process parameters are shown in Table 2. Then, appropriate amounts of prepared membranes with different formulations were cut and pasted on a conductive table. The microscopic morphology of the fiber membrane was observed using a scanning electron microscope as described in Example 1. The results are shown in Table 2. Figure 7 shown.

[0082] Table 2. Polymer types, formulations and process parameters

[0083]

[0084] Depend on Figure 8 It can be seen that in the fiber membranes prepared by the four prescriptions, the nanoparticles in prescription 1 are all adhered to the fibers and lose their independent particle morphology, and the nanoparticles in prescriptions 2, 3 and 4 are all independently present in the fiber network, but the nanoparticles in prescriptions 2 and 4 are of different sizes and particle agglomeration occurs. Therefore, polyvinyl alcohol (PVA) is selected as the polymer material for the nanofiber membrane.

[0085] 3. In vitro release study of nanoparticle-encapsulated nanofiber membranes

[0086] The prepared FGF-encapsulated nanofiber membrane (FGF / PVA) and the nanofiber membrane encapsulated nanoparticles obtained in Example 5 (ALA@FGF NPs / PVA) were investigated for in vitro release behavior. 15 mg of different samples were weighed respectively, and placed in a 15 mL centrifuge tube containing 10 mL phosphate buffer (pH 6.5) and 0.1% sodium azide. The shaker speed was set to 100 rpm and the water bath temperature to 37°C. 1.0 mL of sample solution was taken at a pre-set time interval and centrifuged at 14000 rpm for 30 min to precipitate the suspended solid sample. 200 μL of the supernatant was taken for detection, and then 200 μL of fresh release medium was added again and the sample solution was resuspended and added to the centrifuge tube. The FGF concentration in the sample was measured using an ELISA kit and substituted into the standard curve to calculate the FGF content. The results are as follows: Figure 8 shown.

[0087] Depend on Fig. 9 It can be seen that FGF / PVA exhibits rapid release characteristics, while ALA@FGF NPs / PVA exhibits a biphasic release curve, namely, an initial burst release (about 2 hours) and a subsequent slow controlled release of the drug (about 360 hours). The burst release behavior can be attributed to the rapid dissolution and diffusion of the drug on the surface of the nanoparticles, and then the drug inside the nanoparticles slowly diffuses into the dissolution medium as the nanoparticles disaggregate. This may be due to the interaction between the ALA molecules on the surface of ALANPs and the Ca 2+ The interaction force is weak, but a strong complexation is generated inside, which can play a role in slowly controlling the release of protein biomacromolecules.

[0088] 4. Application of nanofiber membranes loaded with nanoparticles in the healing of deep burn wounds

[0089] First, male Sprague-Dawley rats were intraperitoneally injected with 10% chloral hydrate (4.0 mL / kg), and the back hair was removed with a shaver and depilatory cream after anesthesia. The model was established using a YLS-5Q desktop temperature-controlled scalding instrument, the scalding temperature was set to 80°C, a 2-cm-diameter arc-shaped metal iron head was selected, the iron head pressure was 10 kPa, and the scalding time was 18 seconds. About 1 hour after the scalding, the completely scalded tissue was removed, and the model of deep III degree scald rat model was completed.

[0090] The rats after modeling were randomly divided into four groups, each with 15 experimental rats. The first group was a negative control group (Control), the second group was given a nanofiber membrane loaded with blank nanoparticles (ALA NPs / PVA) (prepared in Example 5), the third group was given a nanofiber membrane loaded with fibroblast growth factor (FGF / PVA), the fourth group was given a nanofiber membrane loaded with drug-loaded nanoparticles (ALA@FGF NPs / PVA) (prepared in Example 5), and the fifth group was given a commercially available topical fibroblast growth factor A series of dressings were covered on the wound surface, and then a silicone ring was glued around the wound with biological glue to prevent the wound tissue from contracting, and the dressing was fixed with an elastic bandage. Each mouse was housed individually in a cage and given drinking water containing gentamicin sulfate for 14 days. The food and breeding environment were strictly kept clean to prevent the occurrence of wound infection. The wounds were photographed on the 0th, 7th, 14th and 21st days of the experiment. The wound area was measured using ImageJ software, and the wound healing rate was calculated. The results are shown in Figure 2. Fig. 9 As shown, A is a wound photo; B is a statistical analysis of the wound healing rate of each group.

[0091] Wound healing rate (%) = (S 原始 -S 测量 ) / S 原始 ×100%

[0092] from Fig.10 It can be seen that on the 7th day, scabs and blood clots formed on the wound surface of each group, indicating that wound bleeding and exudation were effectively controlled and entered the proliferation stage from the initial inflammatory necrosis stage. On the 14th day, the wound area of ​​each group was reduced, and there was a significant difference in the size of the wound, indicating that each group showed different effects on promoting wound healing. On the 21st day, compared with the Control group, the color around the wound in the ALA@FGF PVA group was close to normal skin, and the wound was close to closure. By measuring the healing area of ​​the wound ( Figure 5 B), it was found that the ALANPs / PVA group also showed a significant effect on promoting wound healing on the 14th and 21st days, which indicates that blank ALA nanoparticles have a certain effect on promoting wound healing. In addition, compared with commercially available products The ALA@FGF NPs / PVA group showed significant effects in promoting wound healing at all stages, which may be due to the fact that the nanoparticles improved the stability of FGF in the wound microenvironment, and the slow release was conducive to its biological activity, promoting the rapid closure of the wound epidermis, and the ALA nanoparticle carrier and FGF played a synergistic therapeutic effect in wound healing.

[0093] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An α-lactalbumin nanoparticle, characterized in that: The nanoparticles are prepared by electrostatic spraying process and complexing α-lactalbumin with calcium ions to obtain α-lactalbumin nanoparticles with stable structure.

2. The α-lactalbumin nanoparticles according to claim 1, characterized in that: The molar ratio of calcium ions to α-lactalbumin is 500:1-10:1; wherein the α-lactalbumin is derived from α-lactalbumin in cow's milk and has a molecular weight of 14.2 kDa.

3. A method for preparing α-lactalbumin nanoparticles according to claim 1, characterized in that: Alpha-lactalbumin and polyoxyethylene are dissolved in water, and after the dissolution, a salt containing calcium ions is added to the system and stirred to obtain a clear and transparent electrostatic spray solution, and then alpha-lactalbumin nanoparticles are obtained by electrostatic spraying; wherein the final concentration of alpha-lactalbumin in the electrostatic spray solution is 2-8wt%, and the final concentration of polyoxyethylene is 0.1-0.7wt%.

4. The method for preparing α-lactalbumin nanoparticles according to claim 3, characterized in that: The electrostatic spraying conditions are as follows: voltage of 15-23 kV, injection speed of 0.11-0.38 mL / h, receiving distance of 10-15 cm, temperature of the entire preparation system controlled at 30° C.±3° C., and relative humidity of 50%±5%.

5. An application of the α-lactalbumin nanoparticles according to claim 1, characterized in that: The α-lactalbumin nanoparticles are used as a delivery system.

6. An α-lactalbumin nanoparticle loaded with cell growth factor, characterized in that: The nanoparticles contain the α-lactalbumin nanoparticles according to claim 1.

7. A method for preparing the α-lactalbumin nanoparticles loaded with cell growth factors according to claim 6, characterized in that: Alpha-lactalbumin and polyoxyethylene are dissolved in water, and after the dissolution, calcium ion-containing salt is added to the system and stirred to obtain a clear and transparent electrostatic spray solution. Electrostatic spraying and electrostatic spinning are performed simultaneously to obtain alpha-lactalbumin nanoparticles loaded with cell growth factors.

8. The method for preparing α-lactalbumin nanoparticles loaded with cell growth factors according to claim 7, characterized in that: The working environment temperature of the electrostatic spinning machine is 15° C.-35° C., and the working humidity is 35%-75%.

9. Use of the α-lactalbumin nanoparticles loaded with cell growth factors according to claim 6, characterized in that: Application of the alpha-lactalbumin nanoparticles loaded with cell growth factors in the preparation of wound healing drugs.

10. The use of α-lactalbumin nanoparticles loaded with cell growth factors according to claim 9, characterized in that: The application of the alpha-lactalbumin nanoparticles loaded with cell growth factors in the preparation of a medicine for healing skin wounds caused by burns and scalds.